Pengaruh Persepsi Manfaat, Persepsi Kemudahan Penggunaan, Persepsi Risiko, Gaya Hidup dan Kepercayaan Terhadap Minat Menggunakan QRIS pada Gen-Z di Purwokerto - Muhammad Fadhiil Maulana; Herni Justiana Astuti; Tri Septin Muji Rahayu; Fatmah Bagis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of perceived usefulness, perceived ease of use, perceived risk, lifestyle, and trust on the intention to use QRIS-based electronic money among Generation Z in Purwokerto. The research employs a quantitative approach with a purposive sampling method. The sample size was determined based on Hair’s criteria, namely five times the number of indicators (5 × 22 indicators), resulting in 110 samples, which were then rounded up to 150 respondents to enhance data accuracy. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) 4.0 approach. The results indicate that perceived usefulness and trust have a positive and significant effect on the intention to use QRIS among Generation Z. However, perceived ease of use and lifestyle were found to have no significant effect on this intention. Furthermore, perceived risk was also found to have no significant influence on the intention to use QRIS. This finding is attributed to the high level of digital literacy and self-efficacy among Generation Z, which leads them to perceive risks as tolerable compared to the benefits offered. The implications of this study suggest that financial service providers should focus their development strategies on strengthening cybersecurity infrastructure to maintain user trust and enhancing functional benefit features that support daily transaction efficiency. Theoretically, this study confirms that for digital natives, ease of use is no longer a major barrier due to their high digital literacy capacity. In addition, as QRIS usage has become an inclusive necessity rather than merely a lifestyle symbol, MSME actors are encouraged to provide this system to meet the public’s need for practical daily transactions